Modification of FeCoNi1.5CrCuP/2024Al composites subject to improved aging treatments with cryogenic and magnetic field - Li, G.R.; Zhang, Z.B.; Wang, H.M.; Cao, Z.L.; Liu, J.,Q.; Zhou, Z.C.; Dong, C.; Su, W.X.; Wei, Y.M.; Zhao, H.; Zhou, P.J. (Journal of alloys and compounds, 2023)
High-entropy particles reinforced 2024Al composites exhibit the advantages as prominent particulate performance and metal/metal interfacial strengthening, which is the focused topic in the field of advanced composites. In order to adjust the metastable state of solid-solute samples, a variety of aging treatments of FeCoNi1.5CrCu/2024Al composite were processed incorporating oil bath aging (OBA), deep cryogenic and magnetic field treatment (DCT and MFT) in order to adjust the metastable state of solid-solute samples. The results show that in comparison to sole optimized OBA(170 ℃×10 h) both the DCT and MFT accelerate the aging process, that is, the peak aging can be reached at a lower aging temperature(160 ℃×10 h，DCT-OBA) even a shorter aging time(160 ℃×8 h，MFT+OBA). The optimized DCT-OBA and MFT+OBA samples exhibit the similar characteristic as high compactness, high-density dislocations, voluminous nanometer sub-grains, massive GPB areas and plentiful fine precipitates, small-sized and uniformly distributed HEAP and tight-binding interface. The multiple strength and toughness of the composites are attributed to the significant improvement of comprehensive performance. In comparison to the SS one, the least amplification for the three optimized samples are 10.6 %(compactness), 57.1 %(microhardness),10.0 %(yield strength) and 86.1 %(maximum compression ratio). •Compared with SS and SS-NA, FeCoNi1.5CrCu/2024Al composites subjected to OBA, DCT-OBA and MFT+OBA can effectively improve their comprehensive properties including hardness, compactness, and compression properties. The three optimized samples are OBA(170 ℃×10 h), DCT-OBA((−196 ℃,2 cycles and160℃×10 h) and MFT+OBA(1.5 T,160 ℃×8 h), whose compression properties and maximum compression ratios are similar. It is thought that the DCT and MFT can take the effect of accelerating the aging process. That is, the peak aging can be reached at a shorter aging time or a lower aging temperature. The corresponding fracture mode exhibits as ductile one.•In the DCT, MFT involved samples, because of the shrink force, magnetic pressure and magneto plastic effect, the micro plastic deformation will happen. The induced high-density dislocation leads to the lattice distortion, release of internal stress and energy, which results in the improvement of diffusion kinetics and the closer interatomic bonding and higher compactness. Importantly, the DCT and MFT accelerate the defect formation of supersaturation points, which provide nucleation points for precipitating process in HEA system and fine θ, S phases.•For the DCT or MFT involved samples they are subject to micro plastic deformation, small-sized and uniform distributed HEAP, high dislocation density, voluminous nanometer sub-grains, massive GPB areas, plentiful fine precipitates, tighter interface bonding are the main characteristics. The high compactness, particles reinforcing, dislocation strengthening, fine grain strengthening, GPB and precipitating strengthening and interfacial strengthening, multi strengthening-toughness factors, account for the improvement of comprehensive properties.